The hidden curriculum in a Filipino pre-service physical educators’ virtual ecology - Ortega, Hans Christian; Castro, Rodel; Tolentino, Julius Ceazar; Pusung, DyjÃ±hlhyn Syrh; Abad, Ronalyn (UIR Press Bekerjasama dengan International Association of Physical Education and Sports, 2022)
The study was geared toward determining the factors embedded in “hidden curricula” in an online learning environment of a physical education teacher education program. This qualitative-descriptive study considered a complete enumeration of the Bachelor of Physical Education students from a state university in Pampanga, Philippines who voluntarily participated in this qualitative investigation (n = 135) by responding to structured and open-ended questions. Aided by Thematic Analysis, findings revealed six emerging themes that described the embedded hidden curricula in the online learning environment, namely: contributory factors in an online learning experience (OLEx); educational opportunities in the new normal learning set-up; unfavorable factors in using online learning environment; and proposed inputs in enhancing the teaching-learning process in an OLEx. The implications derived as an outgrowth of the identified positive and negative factors as expressed by the participants provided a conceptual understanding of the contemporary picture of the hidden curricula and how it would define the future of an effective online learning experience.